Evaluation and analysis of SDG reporting: evidence from Africa - Erin, Olayinka Adedayo; Bamigboye, Omololu Adex (Journal of accounting & organizational change, 2022)
Purpose The 2030 Agenda and the sustainable development goals (SDG) have gained considerable attention in research and public debate. This calls for accounting research on the subject of SDG disclosure. Based on this premise, this paper aims to evaluate and analyze the extent of SDG reporting by 80 listed firms from 8 selected African countries for the period of 2016 to 2018. Design/methodology/approach The study adopts a content analysis and survey method to evaluate the extent of SDG reporting by the selected African countries. This paper conducted content analysis through the use of the PricewaterhouseCoopers (PwC) framework and Global Reporting Initiative (GRI) framework to gauge the extent of firms’ compliance with SDG reporting. Also, this paper uses the business reporting indicators for each SDG developed by GRI to determine the compliance level of the selected firms regarding SDG reporting. The survey was targeted at the big four audit firms (PwC, KPMG, Ernst and Young and Deloitte and Touche). Findings The evaluation of SDG disclosure by the 80 listed firms in Africa is still at a very low level except for South African firms. Also, the findings of the business reporting indicators for each SDG target show that most of the firms show little or no concern to report on SDG activities. The result of the research survey indicates that voluntary disclosure, lack of management commitment, lack of regulatory enforcement and cost implications account for low SDG disclosure by the selected African firms. Research limitations/implications This study fails to consider the qualitative research approach in determining the extent of SDG disclosure in Africa, as the study did not allow respondents to freely express their opinion on SDG disclosure, as a large part of the survey used close-ended questionnaires. Practical implications This study’s findings call for clear responsibility and a strong drive for SDG performance from corporate institutions in Africa. While the overall responsibility rests on the government, the actualization of SDG cannot be achieved without support from corporate organizations. The empirical approach used in this study emphasizes the need for corporate organizations to embrace sustainable practices and to integrate SDG information into their reporting cycle. Originality/value This study contributes to growing literature in the area of corporate reporting, sustainability reporting and SDG research in Africa and other emerging economies. Also, this study provides original insight into the contribution of accounting research toward the achievement of SDG.